Training non-physician anaesthetists in sub-Saharan Africa: a qualitative investigation of providers' perspectives. Issue 3 (7th March 2019) - Edgcombe, Hilary; Baxter, Linden S; Kudsk-Iversen, Soren; Thwaites, Victoria; Bulamba, Fred
Abstract : Objectives: To explore the views of non-physician anaesthesia providers (NPAPs) and their colleagues regarding the effectiveness of NPAP training programmes in three contrasting sub-Saharan African countries. Design: This was a qualitative exploratory descriptive study. Semistructured interviews were conducted online, recorded, transcribed and analysed thematically using NVivo. Setting: Participants' homes or workplaces in Sierra Leone, Somaliland and Uganda. Participants: 15 NPAPs, physician anaesthetists and surgeons working in the countries concerned. Results: Three major themes were identified: (1) discrepancy between urban training and rural practice, (2) prominent development of attitudes outside the curricular set during training, including approaches to learning and clinical responsibility and (3) the importance of interprofessional relationships developed during training for later practice. Conclusions: Anaesthesia providers in different cadres and very different country contexts in sub-Saharan Africa describe common themes in training which appear to be significant for their later practice. Not all these issues are explicitly planned for in current training programmes, although they are important in the view of providers. Subsequent programme development should consider these themes with a view to enhancing the safety and quality of anaesthesia practice in this context.